Environmental and individual predictors of 25-hydroxyvitamin D concentrations in Denmark measured from neonatal dried blood spots: the D-tect study. Issue 5 (30th January 2019) - Keller, Amélie; Frederiksen, Peder; Händel, Mina N.; Jacobsen, Ramune; McGrath, John J.; Cohen, Arieh S.; Heitmann, Berit L.
Abstract: Environmental factors such as sunshine hours, temperature and UV radiation (UVR) are known to influence seasonal fluctuations in vitamin D concentrations. However, currently there is poor understanding regarding the environmental factors or individual characteristics that best predict neonatal 25-hydroxyvitamin D (25(OH)D) concentrations. The aims of this study were to (1) identify environmental and individual determinants of 25(OH)D concentrations in newborns and (2) investigate whether environmental factors and individual characteristics could be used as proxy measures for neonatal 25(OH)D concentrations. 25-Hydroxyvitamin D3 (25(OH)D3 ) was measured from neonatal dried blood spots (DBS) of 1182 individuals born between 1993 and 2002. Monthly aggregated data on daily number of sunshine hours, temperature and UVR, available from 1993, were retrieved from the Danish Meteorological Institute. The individual predictors were obtained from the Danish National Birth register, and Statistics Denmark. The optimal model to predict 25(OH)D3 concentrations from neonatal DBS was the one including the following variables: UVR, temperature, maternal education, maternal smoking during pregnancy, gestational age at birth and parity. This model explained 30 % of the variation of 25(OH)D3 in the neonatal DBS. Ambient UVR in the month before the birth month was the best single-item predictor of neonatal 25(OH)D3, accounting for 24 % of its variance. Although this prediction model cannot substitute for actual blood measurements, it might prove useful in cohort studies ranking individuals in groups according to 25(OH)D3 status.